The role of seeing blood in non-suicidal self-injury in female patients with borderline personality disorder - Naoum, Janina; Baumgärtner, Ulf; Mancke, Falk; Treede, Rolf-Detlef; Schmahl, Christian (Psychiatry research, 2016)
Patients with Borderline Personality Disorder (BPD) often engage in non-suicidal self-injury (NSSI), to reduce arousal levels under stress. However, the importance of seeing blood for the effect of NSSI is yet unknown. The present pilot study examined 20 female BPD patients and 20 healthy controls (HC) to assess the role of seeing blood on arousal, pain, urge for NSSI (ratings) and heart rate (continuously measured). Participants completed two sessions consisting of stress induction (forced mental arithmetics with white noise), followed by a seven second non-invasive pain stimulus with a blade to the volar forearm. At one session, only the painful blade stimulus was applied, at the other, artificial blood was added. For arousal, a significantly stronger decrease was revealed in the BPD than in the HC group, however with no significant effects between blood and non-blood conditions. Concerning urge for NSSI, the BPD showed a significantly greater decrease in blood condition over time than the HC group. Interestingly, heart rate decreased stronger over time in the HC group during the blood condition than in BPD. For tension relief by non-damaging mechanical painful stimulus the addition of visible blood showed neither subjective (arousal, urge for NSSI), nor objective (heart rate) advantages.
Gesehen am 28.03.2019
Available online 2 November 2016